PENINGKATAN KETERAMPILAN MEMBACA PEMAHAMAN TEKS EKSPLANASI SISWA KELAS XI TKR 1 SMK MERDEKA SOREANG - Puji Pamungkas Sari; Ririn Gustari Luciana; Indra Permana (IKIP Siliwangi, 2018)
This class action education is aimed to find out (1) The improvement of reading comprehension students of class XI TKR 1 after being given REAP method, and (2) to know the student's response to the implementation of REAP method in reading comprehension. The subjects of this study were 36 students of class XI TKR 1 SMK Merdeka Soreang. The Data collection in this research is done by giving test, collecting questionnaires, interviews and field observation. The data gathering instruments used include students questionnaires, test results, observation sheets, and interview guidelines. The data obtained were analyzed descriptively quantitative and qualitative. The first research result is the implementation of REAP method can improve students' comprehension of class XI TKR 1 SMK Merdeka Soreang in reading text. The average score of the pre test gain was 62.47, increased to 69.78 in the post test 1, and 75.67 in the post test 2. The second study result is the student's response to the REAP method in this reading comprehension is very positively. Students feel helped by the use of this REAP method.